FLUID CHALLENGE TEST IN NORMAL SUBJECTS AND IN A HETEROGENEOUS POPULATION WITH PULMONARY HYPERTENSION - D’Alto, Michele; Romeo, Emanuele; Argiento, Paola; Di Marco, Giovanni M.; Correra, Anna; Sarubbi, Berardo; Russo, Maria G.; Naeije, Robert (Journal of the American College of Cardiology, 2016)
Right atrial pressure (RAP), systolic, mean and diastolic pulmonary arterial pressure (SPAP, MPAP and DPAP), pulmonary arterial wedge pressure (PAWP), cardiac index (CI), diastolic pulmonary gradient (DPG) and pulmonary vascular resistance (PVR) were calculated at baseline and immediately after FCT.